Differentiation of homicidal or suicidal strangulation. (August 2019) - Doberentz, E.; Markwerth, P.; Madea, B.
Highlights: The differentiation between suicidal, accidental and homicidal hanging cases can be very challenging. The majority of hanging cases have suicidal background. In hanging cases a thorough crime scene investigation and autopsy is essential. Further investigations subsequent to the autopsy are required. Abstract: Hanging can be suicidal, accidental, or homicidal, and these backgrounds must be discriminated by police and forensic pathologists. We herein report a case involving a 33-year-old man who was found dead on the floor behind the entrance door of an apartment house. The man's brother declared that he had found him hanging in the gap between the stairs on the top floor. When his brother tried to cut him down, the victim fell three floors down through the gap between the stairs. Autopsy was performed to confirm suicidal hanging and a postmortem fall into the narrow gap. In this case, however, a homicide was suspected, and the version of events told by the victim's brother was initially doubted. Homicidal hanging may be uncommon, but intensive scene investigation and thorough autopsy are necessary in hanging cases to rule out homicide.